Resolving Serious Violations of Human Rights in Non-Judicial Mechanisms in Indonesia - Syaiful Rohman; Harkristuti Harkrisnowo (West Science Law and Human Rights, 2024)
Protection and respect for human rights is the state's responsibility, especially the government. The state is morally and politically responsible for ending the nation's wounds to create harmony in national and state life. Therefore, the government is obliged to resolve cases Serious Violations of Human Rights either judicially or non-judicially. Legislation has outlined that Serious Violations of Human Rights can be resolved through judicial and non-judicial mechanisms. The government has issued various policies to resolve Serious Violations of Human Rights through non-judicial mechanisms that aim to focus on recovering victims. This research uses qualitative methods using credible and relevant data sources. This research shows that non-judicial resolution Serious Violations of Human Rights is a middle way to provide a sense of justice to victims. The state is responsible and provides victims' rights through a reconciliation process to create harmony among society in the nation and state.